2017
DOI: 10.1159/000481236
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Adenosquamous Carcinoma Associated with Primary Sclerosing Cholangitis

Abstract: Introduction: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disorder characterized by multiple fibrotic strictures of the bile duct. More than 40% of deaths in PSC patients are related to malignant tumors, including cholangiocarcinoma. Primary hepatic adenosquamous carcinoma (ASC) is a rare subtype of cholangiocarcinoma containing adenocarcinoma (AC) and squamous cell carcinoma (SCC) components, with a poorer prognosis than other cholangiocarcinomas. We report the first case of a hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Owing to tissue necrosis associated with primary hepatic ASC, it can be easily confused with the liver abscess in the imaging data. Therefore, tissue pathology should be conducted to confirm the diagnosis of primary hepatic ASC [ 1 , 23 27 ]. In the present case, we suspected a liver abscess initially as the patient was febrile, had elevated inflammatory markers, and his CT scan showed a low-density area in the center of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to tissue necrosis associated with primary hepatic ASC, it can be easily confused with the liver abscess in the imaging data. Therefore, tissue pathology should be conducted to confirm the diagnosis of primary hepatic ASC [ 1 , 23 27 ]. In the present case, we suspected a liver abscess initially as the patient was febrile, had elevated inflammatory markers, and his CT scan showed a low-density area in the center of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The available information on all the 72 cases (including our case) is summarized in Fig. 6 [ 1 , 2 , 6 , 7 , 16 21 , 23 – 46 ]. The patients in previously reported cases included 42 males and 30 females, with ages 28 through 85 years (median age: 65 years).…”
Section: Discussionmentioning
confidence: 99%
“…ASC contains both adenocarcinoma and squamous cell carcinoma components, tends to present more aggressive clinicopathologic features, and has a poorer prognosis than other cholangiocarcinomas. Yamao et al [14] first reported the first case of hepatic ASC in a patient with PSC. They concluded that patients with PSC should be recognized as being at risk of hepatic ASC, in addition to general cholangiocarcinoma, hepatocellular carcinoma (HCC), and metastatic liver tumor.…”
mentioning
confidence: 99%